1H‐1, 2, 3‐triazole embedded Isatin‐Benzaldehyde‐bis(heteronuclearhydrazones): design, synthesis, antimycobacterial, and cytotoxic evaluation. (25th November 2021) - Sharma, Bharvi; Kumar, Sumit; Preeti,; Johansen, Matt D.; Kremer, Laurent; Kumar, Vipan
Abstract: Rapid growth of global drug‐resistant tuberculosis and urgent requirement for short treatment regimens is stimulating the need for discovery of new TB drugs. In this work, we report the design, synthesis and in vitro antimycobacterial evaluation of a library of isatin‐derived bis(heteronuclear hydrazones). Evaluation results revealed that the inclusion of isoniazid core into 1 H ‐1, 2, 3‐triazole tethered isatin‐benzaldehydes improved the antimycobacterial activity on tuberculosis mc 2 6230 strain and significantly reduced the cytotoxicity against Vero cells. However, the introduction of semicarbazones/thiosemicarbazones or pyrazine‐2‐carbohydrazide produced the opposite effects. The compounds with isoniazid and polar‐donating groups at the C‐5 position of isatin emerged as the most promising conjugates with MIC99 = 0.36 µg/ml. The most active compounds were non‐cytotoxic to Vero cells (IC50 >100 µg/ml) with selectivity indices >277. Abstract : Isatin‐benzaldehyde‐bis(heteronuclear hydrazones) were synthesized and evaluated as anti‐mycobacterials. The introduction of isoniazid improved the activity and reduced cytotoxicity. The most promising and non‐cytotoxic conjugates 14c and 14e exhibited MIC99 0.36 µg/ml. The most potent conjugate demonstrated a selectivity index > 277.